Kajian Mewujudkan Angkutan Umum Perkotaan Yang Tertib Di Wilayah Bekasi - Sulianti, Rini (Warta Penelitian Perhubungan, 2010)
flats, shops, banks, and restaurants that stood here. Bekasi also be an option for citizens wlw want totravel Jabotabek shopping, because there are side Mal Metropolitan, Mega Hypermal Bekasi, BekasiSquare, Plam Pondok Gede, Grand Mall, Bekasi Cyber Park, and Bekasi Trade Centre. Shoppingcenters such as Oirrefour Jn;pemzarket, Giant, Makro, and Hypermarl also present in Luxun; residentialtownship with too many amenities to grow here, like Kemang Pratama, Harapan Indah andSumarikon and the many traditional markets. With the development of Bekasi cihj in tenns of economicand population growth will affect the increasing number of vehicles, including personal auto-1nobile, motorci;cle and car of two-wheeled transport is spread all aver the city in the area of Bekasi,even ranked third Jabotabek se with an increased number of motor vehicles Most after Tangerang andWest Jakarta. This becomes a problem in the Bekasi area makes the region particularly bad in themorning and afternoon hares dmj so road users are not comfortable, safe and smoothly to achieve thegoal. For that is needed for "Polia; Studies Solve Traffic Congestion in the area of Bekasi" In order toimprove service to the user traffic Bekasi area.